A Regularity Criterion for the 3D Incompressible Magnetohydrodynamics Equations in the Multiplier Spaces. (27th August 2017) - Tian, Chunhong
Abstract : We are concerned with the regularity criterion for weak solutions to the 3D incompressible MHD equations in this paper. We show that if some partial derivatives of the velocity components and magnetic components belong to the multiplier spaces, then the solution actually is smooth on ( 0, T ) .